Conquering Relevance: Entrepreneurship Research's Grand Challenge. (May 2019) - Wiklund, Johan; Wright, Mike; Zahra, Shaker A.
Entrepreneurship research has grown rapidly in its scope, rigor, and impact. By every measure, our field now enjoys considerable academic acceptance and legitimacy as a scholarly discipline. However, several forces around the globe are demanding greater attention to (and perhaps redefinition of) relevance. We discuss what relevance means, how the field can achieve it, and how to best communicate it to the diverse stakeholders of our field.